Nursing Care for An.A with Febrile Illness at the National Defense Central Hospital (RSPPN) Panglima Besar Soedirman - Fayza Shaffa Zahira; Herlina (CV. CENDIKIA JENIUS INDONESIA, 2025)
Background: Fever is a physiological reaction of the body to infection or problems in the immune system, characterized by an increase in body temperature above 37.5°C. In children, fever can cause serious problems such as seizures, dehydration, and decreased level of consciousness. It is important to carry out proper treatment so that these complications do not occur. Objective: How is the implementation of nursing care for children with fever using non-pharmacological intervention Tepid Water Sponge. Research Method: This study used a case study method in one case of a child with sub febrile. Data were obtained through interviews, observations, physical examinations, and documentation analysis. Results: The identified nursing diagnoses included hyperthermia, risk of hypovolemia, and nausea. Implementation of independent nursing, namely Tepid Water Sponge for 15 minutes, showed a response of a decrease in body temperature of 0.4°C. Most nursing problems have been resolved, except for the risk of widespread infection. Conclusion: the implementation of nursing care has been in accordance with the nursing plan. Suggestion: The researcher suggests continuing nursing care to address the problem of the risk of widespread infection.